2010
DOI: 10.1007/s00535-010-0343-0
|View full text |Cite
|
Sign up to set email alerts
|

Size of mural nodule as an indicator of surgery for branch duct intraductal papillary mucinous neoplasm of the pancreas during follow-up

Abstract: A mural nodule of 10 mm is appropriate as an indicator of surgery in the follow-up of branch duct IPMN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(39 citation statements)
references
References 25 publications
2
36
1
Order By: Relevance
“…On the other hand, high-risk stigmata, including jaundice, malignant cytology and dilated MPD, were strongly associated with malignancy and decreased survival. We failed to identify enhancing nodules, a well-known feature associated with invasive carcinoma in IPMNs,6 9–10 28 32 as an independent predictor of survival in all the analysis carried out in the study. This observation, however, should be considered with caution because the study is retrospective, and overall nodules and enhancing nodules were identified in only 48 (17%) and 22 patients (8%), respectively, and it is possible that the presence of nodules at diagnosis had prompted clinicians to operate patients without any delay.…”
Section: Discussionmentioning
confidence: 88%
“…On the other hand, high-risk stigmata, including jaundice, malignant cytology and dilated MPD, were strongly associated with malignancy and decreased survival. We failed to identify enhancing nodules, a well-known feature associated with invasive carcinoma in IPMNs,6 9–10 28 32 as an independent predictor of survival in all the analysis carried out in the study. This observation, however, should be considered with caution because the study is retrospective, and overall nodules and enhancing nodules were identified in only 48 (17%) and 22 patients (8%), respectively, and it is possible that the presence of nodules at diagnosis had prompted clinicians to operate patients without any delay.…”
Section: Discussionmentioning
confidence: 88%
“…With an overall risk of malignant transformation estimated at 6-40%, a close surveillance of BD-PMN seems reasonable except if predictive factors of malignancy are present or appear during follow-up. [2][3][4][5][6][7] In order to propose a management algorithm of BD-IPMN, the International Consensus Guidelines (ICG) have been updated recently in 2012 and categorized predictors of malignancy as high-risk stigmata and worrisome features. 8 High-risk stigmata include (a) obstructive jaundice, (b) enhanced solid component, and (c) dilation of the main pancreatic duct (MD) to a diameter greater than 10 mm.…”
Section: Introductionmentioning
confidence: 99%
“…10,26,27 Among these characteristics, a large mural nodule is considered to be the most reliable predictive factor. 27,28 The present study is the first to indicate that fibrosis and the expression of matricellular proteins in the periductal stroma are useful for predicting the histological grade of IPMN. Based on these results, the histological grade of IPMN with marked stromal fibrosis is more likely to be high-grade dysplasia or IPMN with an associated invasive carcinoma.…”
Section: Discussionmentioning
confidence: 99%